Meningkatkan Kompetensi Masyarakat Pesisir dalam Budidaya Kepiting Bakau: Penerapan Sistem Apartemen dan RAS di Desa Persiapan Empol, Sekotong, Lombok Barat - Setyono, Bagus Dwi Hari; Junaidi, Muhammad; Diniariwisan, Damai; Sumsanto, Muhammad; Cokrowati, Nunik; Saputra, Ardyen (Universitas Mataram, 2024)
This community service project was conducted in Persiapan Empol Village, Sekotong District, West Lombok Regency, to enhance the knowledge and skills of local communities in mud crab (Scylla spp.) farming using the apartment system and recirculating aquaculture system (RAS). The village is rich in natural resources, particularly in fisheries, but limited knowledge has been a major obstacle in developing aquaculture practices. The method used in this project was a demonstration plot involving 15 members of the